2013
DOI: 10.1186/1748-5908-8-109
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing pharmacists’ adoption of prescribing: qualitative application of the diffusion of innovations theory

Abstract: BackgroundIn 2007, Alberta became the first Canadian jurisdiction to grant pharmacists a wide range of prescribing privileges. Our objective was to understand what factors influence pharmacists’ adoption of prescribing using a model for the Diffusion of Innovations in healthcare services.MethodsPharmacists participated in semi-structured telephone interviews to discuss their prescribing practices and explore the facilitators and barriers to implementation. Pharmacists working in community, hospital, PCN, or ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
118
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(129 citation statements)
references
References 31 publications
6
118
1
4
Order By: Relevance
“…This was in agreement with other studies which stated that pharmacists 'recognised the need and expressed desire' to have management support to take prescribing forward. 12,21 Pharmacy managers set and promote the culture towards education and training in their hospitals and act as role models for colleagues. Their leadership in establishing direction, motivating and supporting their staff are all important both during the PLP and for future service delivery.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This was in agreement with other studies which stated that pharmacists 'recognised the need and expressed desire' to have management support to take prescribing forward. 12,21 Pharmacy managers set and promote the culture towards education and training in their hospitals and act as role models for colleagues. Their leadership in establishing direction, motivating and supporting their staff are all important both during the PLP and for future service delivery.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…There were similar conclusions in previous studies which found that pharmacists who networked with other colleagues and networks had more active prescribing practices. 12,21 Active PIPs were more likely to have felt well supported by the MDT during their PLP than those not prescribing (p < 0.05). It is important that there is support from the MDT during the PLP to ensure successful implementation of prescribing.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations